Odpowiedzi

2009-10-12T21:50:24+02:00
X+2/x-2 - 8/x²-2x = 2/x zał:x∈R\{0,2}
x+2/x-2 - 8/x(x-2) = 2/x
wspólny mianownik x(x-2)
(x+2)x/x(x-2) - 8/x(x-2) = 2(x-2)/x(x-2) /x(x-2)
(x+2)x- 8= 2(x-2)
x²+2x-8=2x-4
x²-4=0
x=2 sprzeczne
x=-2

odp.x=-2

2009-10-12T22:13:15+02:00
X+2/x-2 - 8/x²-2x = 2/x zał:x∈R\{0,2}
x+2/x-2 - 8/x(x-2) = 2/x

(x+2)x/x(x-2) - 8/x(x-2) = 2(x-2)/x(x-2) /x(x-2)
(x+2)x- 8= 2(x-2)
x²+2x-8=2x-4
x²-4=0
x=2
x=-2

odp.x=-2
CHYBA BĘDZIE DOBRZE ,TRUDNO PISZE SIĘ BEZ KRESEK UŁAMKOWYCH.
1 5 1